Ectodomain shedding of CD99 within highly conserved regions is mediated by the metalloprotease meprin β and promotes transendothelial cell migration. Issue 3 (21st December 2016) - Bedau, Tillmann; Peters, Florian; Prox, Johannes; Arnold, Philipp; Schmidt, Frederike; Finkernagel, Malin; Köllmann, Sandra; Wichert, Rielana; Otte, Anna; Ohler, Anke; Stirnberg, Marit; Lucius, Ralph; et al.
ABSTRACT: The adhesion molecule CD99 is essential for the transendothelial migration of leukocytes. In this study, we used biochemical and cellular assays to show that CD99 undergoes ectodomain shedding by the metalloprotease meprin β and subsequent intramembrane proteolysis by γ‐secretase. The cleavage site in CD99 was identified by mass spectrometry within an acidic region highly conserved through different vertebrate species. This finding fits perfectly to the unique cleavage specificity of meprin β with a strong preference for aspartate residues and suggests coevolution of protease and substrate. We hypothesized that limited CD99 cleavage by meprin β would alter cellular transendothelial migration (TEM) behavior in tissue remodeling processes, such as inflammation and cancer. Indeed, meprin β induced cell migration of Lewis lung carcinoma cells in an in vitro TEM assay. Accordingly, deficiency of meprin β in Mep1b −/− mice resulted in significantly increased CD99 protein levels in the lung. Therefore, meprin β could serve as a therapeutic target, given that in a proof‐of‐concept approach we showed accumulation of CD99 protein in lungs of meprin β inhibitor‐treated mice.—Bedau, T., Peters, F., Prox, J., Arnold, P., Schmidt, F., Finkernagel, M., Köllmann, S., Wichert, R., Otte, A., Ohler, A., Stirnberg, M., Lucius, R., Koudelka, T., Tholey, A., Biasin, V., Pietrzik, C. U., Kwapiszewska, G., Becker‐Pauly, C. Ectodomain shedding of CD99 within highly conserved regions is mediated by the metalloprotease meprin β and promotes transendothelial cell migration. FASEB J. 31, 1226–1237 (2017). www.fasebj.org